Pregnancy outcome following spontaneous abortions - Agrawal, Swati; Agrawal, Veena; Suhane, Rajni (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: The objective of the present study was to study pregnancy outcome in patients with history of previous spontaneous abortions. Methods: A prospective study included patients with history of previous spontaneous abortion admitted in the Department of Obstetrics and Gynaecology, GR Medical College and Kamla Raja Hospital, Gwalior between September 2008 and February 2009. The patients were either booked (minimum 3 visits in antenatal outdoor clinic) or admitted for the first time as an emergency. The detailed history about previous abortions was taken and routine as well as investigations for possible etiologies of previous abortions were done. Cases with history of mid-trimester abortion were investigated for cervical incompetence. All the patients were observed for complications during present pregnancy like threatened abortion, preeclampsia, preterm labour, intrauterine death and final outcome. Results: A total of 70 patients with history of previous spontaneous abortion were admitted, out of which 40 (57.2%) patients were booked and 30 (42.8%) reported first time in emergency. Majority (57.1 %) of patients belong to the age group 21-29 years. Educational status of the patients showed 61.4% had no formal education or only up to primary level. Anemia was found to be very severe in 4.3 %, severe in 10% and moderate in 30 % patients. Maximum patients (45.7%) were with history of previous one abortion followed by previous two abortions (38.6%). Incidence of abortions after one, two, three and four abortions was 9.4, 14.8, 20 and 100 percent respectively. The final outcomes were term live birth (74.3%), abortion (14.3%), preterm delivery (8.6%), and still birth (2.8%). In the present study 10 (14.3%) pregnancies ended with abortion, out of which 4 were in booked and 6 in emergency patients. Live babies were of 90% booked mothers whereas 70% in emergency patients. Caesarian section was done in 23.3% patients for various indications. Conclusions: Previous history of spontaneous abortion is associated with adverse pregnancy outcome. There is increased risk of abortion, preterm delivery, need for caesarean sections and fetal loss in cases of previous spontaneous abortions. These complications and fetal loss can be reduced by booking the patients and giving due antenatal care.